IN VITRO ANTIBACTERIAL ACTIVITY OF EUCALYPTUS (Melaleuca leucadendra) OIL AGAINST METHICILLIN-RESISTANT Staphylococcus aureus (MRSA) - Constantia Lidwina Targanski; Wiwin Retnowati; Mohammad Fathul Qorib; Manik Retno Wahyunitisari; Wilda Mahdani (Universitas Airlangga, Surabaya, Indonesia, 2023)
Highlights The use of eucalyptus oil is natural and risk-free. It has a lengthy history of use as a traditional medicine in Asia, including Indonesia. It has been demonstrated that eucalyptus oil possesses antibacterial activity against MRSA, and this activity was controlled by the oil's concentration. Abstract Background: Eucalyptus (Melaleuca leucadendra) oil is used by Indonesians as an herbal medicine. Eucalyptus containing 1,8-cineol at 72.30% is expected to be used as an antibacterial. Â Objective: The study aimed to assess the antibacterial activity of eucalyptus oil against Methicillin-resistant Staphylococcus aureus (MRSA) bacteria in vitro. Material and Method: The materials used were eucalyptus oil (M. leucadendra) in various concentrations with ethyl acetate as solvent. The research method used was the agar-well diffusion assay. The MRSA was suspended to 0.5 McFarland turbidity. The MRSA suspension was thoroughly swabbed onto the surface of the Mueller-Hinton agar plate. The wells were made with a diameter of 0.6 mm on Muller-Hinton agar aseptically and 100 Âµl of eucalyptus oil was put into the well using a micropipette and incubated for 24 hours at 37Â°C. The diameter of the inhibition zone was measured with a caliper. Statistical analysis using the SPSS software edition 23. Result: Eucalyptus oil solution starting from a concentration of 10% to 100% had an antibacterial response, which could be seen by the formation of a bacterial inhibition zone around the eucalyptus oil (M. leucadendra) wells. The inhibition ability of eucalyptus oil against MRSA bacteria was greatest at a concentration of 90% with an inhibition zone of 31.26 mm. It was found that the concentration of eucalyptus oil affected the diameter of the bacterial inhibition area. Conclusion: Eucalyptus oil has been shown to have antibacterial activity against MRSA and was influenced by the concentration of the oil.